b - Collins, Suzanne (New York : Scholastic Press, 2009)
Against all odds, Katniss has won the Hunger Games. She and fellow District 12 tribute Peeta Mellark are miraculously still alive. Katniss should be relieved, happy even. After all, she has returned to her family and her longtime friend, Gale. Yet nothing seems right. Gale holds her at an icy distance. Peeta has turned his back on her completely. And there are whispers of a rebellion against the Capitol - that Katniss and Peeta may have helped create
Keywords: Survival -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction. -- Fi